2020
DOI: 10.3389/fphys.2020.01050
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia in Kidney Disorders: Perspectives on Mitochondria Homeostasis and Therapeutic Opportunities

Abstract: To excrete body nitrogen waste and regulate electrolyte and fluid balance, the kidney has developed into an energy factory with only second to the heart in mitochondrial content in the body to meet the high-energy demand and regulate homeostasis. Energy supply from the renal mitochondria majorly depends on lipid metabolism, with programed enzyme systems in fatty acid β-oxidation and Krebs cycle. Renal mitochondria integrate several metabolic pathways, including AMPK/PGC-1α, PPARs, and CD36 signaling to maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 169 publications
0
16
0
Order By: Relevance
“…Fatty acids are the most powerful substrates for adenosine triphosphate production, while the kidney is one of the major organs with a high demand for energy to maintain its metabolic activities. In particular, the renal proximal tubule, which contains abundant mitochondria, primarily relies on fatty acids as an energy source [ 59 ]. Therefore, proximal tubular cells are vulnerable to dysregulated mitochondrial fatty acid oxidation.…”
Section: Mechanisms Underlying the Renoprotective Effect Of Sglt2 Inhibitorsmentioning
confidence: 99%
“…Fatty acids are the most powerful substrates for adenosine triphosphate production, while the kidney is one of the major organs with a high demand for energy to maintain its metabolic activities. In particular, the renal proximal tubule, which contains abundant mitochondria, primarily relies on fatty acids as an energy source [ 59 ]. Therefore, proximal tubular cells are vulnerable to dysregulated mitochondrial fatty acid oxidation.…”
Section: Mechanisms Underlying the Renoprotective Effect Of Sglt2 Inhibitorsmentioning
confidence: 99%
“…The kidney is one of the most energy-demanding organs in the human body, and numerous studies have shown that the kidney mainly uses fatty acid oxidation (FAO) as its energy source ( 7 ). Because fatty acids (FAs) metabolism produce 3 times more adenosine triphosphate (ATP) than glucose ( 8 ).…”
Section: Lipid Metabolism In the Renal Tubulementioning
confidence: 99%
“…Renal FAO occurs mainly in mitochondria, and tubular cells contain a large number of mitochondria ( 10 ). For example, the human proximal convoluted tubules contain abundant large mitochondria, which occupy about 16.3% cell volume ( 7 ). Thus, renal tubules are the core site of renal energy metabolism ( 10 ).…”
Section: Lipid Metabolism In the Renal Tubulementioning
confidence: 99%
See 2 more Smart Citations